2016
DOI: 10.1021/acssuschemeng.6b01302
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Aromatic Copolyesters via Ring Opening Polymerization: Poly(butylene 2,5-furandicarboxylate-co-terephthalate)s

Abstract: A series of poly­(butylene 2,5-furan­dicarboxylate-co-terephthalate) copolyesters coPBF x T y covering the whole range of compositions has been prepared via ring opening polymerization (ROP). Cyclic oligomers of butylene 2,5-furan­dicarboxylate c(BF) n and butylene terephthalate c(BT) n , both mainly consisting of a mixture of dimer, trimer, and tetramer species, were synthesized by the high dilution condensation method. Random copolyesters with the targeted compositions and weight-average molecular weights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 37 publications
3
46
0
Order By: Relevance
“…In addition, the fast kinetics observed for the entropically‐driven ROP of CBT, within minutes, enables a variety of techniques to be employed, such as reaction injection molding (RIM), resin transfer molding (RTM) or rotational molding (RM) . Complementary to their use as a precursor for thermoplastic matrix in composites, CBT has also been polymerized with the aim at producing nano‐composites, polymer blends, or copolymers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the fast kinetics observed for the entropically‐driven ROP of CBT, within minutes, enables a variety of techniques to be employed, such as reaction injection molding (RIM), resin transfer molding (RTM) or rotational molding (RM) . Complementary to their use as a precursor for thermoplastic matrix in composites, CBT has also been polymerized with the aim at producing nano‐composites, polymer blends, or copolymers …”
Section: Introductionmentioning
confidence: 99%
“…9 Complementary to their use as a precursor for thermoplastic matrix in composites, CBT has also been polymerized with the aim at producing nano-composites, 12,13 polymer blends, 14,15 or copolymers. 16,17 Because PBT shows high resistance to solvents, low moisture absorption and good mechanical properties at high temperature, it also represents an attractive candidate for the synthesis of thermoplastic elastomers. Nevertheless, only Chen et al have reported the synthesis of PBT-based triblock copolymers by ROP of CBT.…”
mentioning
confidence: 99%
“…8 However the access to cyclic (alkylene 2,5-furandicarboxylate) oligomers [c(EF) n and c(BF) n ] recently afforded by chemical synthesis has opened the ROP route toward the preparation of these polyesters. 13,14 Additionally, aromatic copolyesters made of butylene furanoate (BF) and butylene terephthalate (BT), 15 as well as aromatic-aliphatic copolyesters made from BF and butylene succinate (BS) 16 have been prepared by ROP in good yields with pretty high molecular weights. In these copolymerizations cyclic (BT) and (BS) oligomers were the respective Additional Supporting Information may be found in the online version of this article.…”
mentioning
confidence: 99%
“…The interest in polymers derived from HMF and its derivatives has been rapidly increasing not only due to the sustainability and rich chemistry of HMF, but also due to the unique properties of these polymers. Currently, the preparation of HMF derivatives‐based polymers are mainly performed via chemical approaches . Enzymatic catalysis routes have been recently evaluated as well .…”
Section: Polymers Derived From Hmf and Its Derivativesmentioning
confidence: 99%
“…Currently, the preparation of HMF derivatives-based polymers are mainly performed via chemical approaches. 33,[121][122][123] Enzymatic catalysis routes have been recently evaluated as well. 53 Therefore, in this section, the synthesis and characterization of polymers via chemical methods will be reviewed, starting from three key monomers (FDCA, BHF, and DFF).…”
Section: Polymers Derived From Hmf and Its Derivativesmentioning
confidence: 99%